Pengaruh E-Service Quality Dan E-Trust Terhadap Kepuasan Pelanggan Pengguna Moda Transportasi Grab di Tangerang Selatan - Edi Setiawan; Sarah Septiani (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2018)
In this research used survey method, that is to explain influence between independent variable that is electronic service quality and electronic trust to dependent variable that is customer satisfaction and explain relation between variable. The population in this study is the consumer of Grab Car transport users in Bintaro, South Tangerang. The sampling technique uses accidental technique, ie random sampling of the sample that met on that day. Technique of collecting data that is done is test of questioner, that is data collecting technique by asking some direct statement to sample. Processing techniques and data analysis include correlation analysis, multiple linear regression analysis, classical assumption test, hypothesis test and coefficient of determination analysis. The result of T test statistic shows that the quality of electronic service partially has significant effect on customer satisfaction. Electronic confidence partially significant effect on customer satisfaction, while statistical test F shows the quality of electronic services and electronic trust simultaneously significant effect on customer satisfaction.